Pemenuhan Hak Ganti Rugi Bagi Anak Korban Kekerasan Seksual - Adri, Nadita; Najemi, Andi; Monita, Yulia (Faculty of Law, Universitas Jambi, 2024)
This article aims to analyze the fulfillment of the exercise of the right to restitution or compensation for child victims of sexual violence and the factors that impede the exercise of the right to restitution or compensation by child victims of sexual violence. Indecent or immoral acts and sexual harassment or sexual harassment are two forms of ethical behavior that are not only a matter of national law in a country, but have become legal issues in the United States, other countries in all countries in the world or have become global problems. The research results of this article are victims of sexual violence not only among adults but also those who are classified as minors (children). The low biological condition of children makes it easier for criminals to commit crimes against children and makes them the most vulnerable victims. It can be said that the application of efforts to exercise the right to compensation for victims of criminal acts has not been optimal in upholding these rights in the justice system. Victims of criminal acts are entitled to compensation in the form of compensation for property or income losses, compensation for losses suffered as a result of suffering directly related to the crime, and/or reimbursement for medical and/or psychological expenses, but laws and regulations do not specifically regulate guarantees, property rights and rights to compel the perpetrator to compensate the victim for losses resulting in the negligence of the perpetrator in carrying out his obligations without doing optimally for the victim to seek justice for his actions. guilty. Abstrak Artikel ini bertujuan untuk menganalisis pemenuhan atas pelaksanaan hak restitusi atau ganti rugi anak korban kekerasan seksual dan faktor-faktor yang menghambat pelaksanaan hak atas restitusi atau ganti rugi oleh anak korban kekerasan seksual. Perbuatan tidak senonoh atau tidak bermoral dan pelecehan seksual atau pelecehan seksual adalah dua bentuk perilaku etis yang tidak hanya menjadi masalah hukum nasional suatu negara, tetapi telah menjadi masalah hukum di Amerika Serikat, negara lain di semua negara di dunia atau telah menjadi masalah global. Hasil penelitian artikel ini adalah korban kekerasan seksual tidak hanya di kalangan orang dewasa tetapi juga mereka yang tergolong anak di bawah umur (anak-anak). Kondisi biologis anak yang rendah membuat pelaku kejahatan lebih mudah melakukan perbuatannya terhadap anak dan menjadikan mereka korban yang paling rentan. Dapat dikatakan bahwa penerapan upaya pelaksanaan hak atas ganti kerugian bagi korban tindak pidana belum optimal dalam penegakan hak tersebut dalam sistem peradilan. Korban tindak pidana berhak mendapat ganti rugi berupa penggantian kerugian harta benda atau penghasilan, penggantian kerugian yang dideritanya sebagai akibat penderitaan yang berkaitan langsung dengan tindak pidana, dan/atau penggantian biaya pengobatan dan/atau psikologis, tetapi peraturan perundang-undangan tidak secara khusus mengatur tentang jaminan, hak milik dan hak untuk memaksa pelaku mengganti kerugian kepada korban yang mengakibatkan kelalaian pelaku dalam menjalankan kewajibannya tanpa melakukan secara optimal bagi korban untuk mencari keadilan atas perbuatannya. bersalah.